Living with cyberspace : technology & society in the 21st century - Armitage, John, 1956-; Roberts, Joanne (Continuum, 2002)
Cyberspace and cybertechnology have impacted on every aspect of our lives. Western society, culture, politics and economics are now all intricately bound with cyberspace. Living With Cyberspace brings together the leading cyber-theorists of North America, Britain and Australia to map the present and the future of cyberspace.Presenting a guidebook to our new world, both the theory and the practice, the book covers subjects as diverse as androids, biotech, electronic commerce, the acceleration of everyday life, access to information, the alliance between the military and the entertainment industries, feminism, democratic practice and human consciousness itself.Together, the essays--divided into separately introduced sections on society , culture, politics and economics--present a systematic and state-of-the-art overview of technology and society in the 21st Century.Contributors: John Armitage, Verena Andermatt Conley, James Der Derian, William H. Dutton, Phil Graham, Tim Jordan, Wan-Ying Ling, David Lyon, Ian Miles, Joanne Roberts, Saskia Sassen, Cathryn Vasseleu, McKenzie Wark, Frank Webster.